Genomic Fusions in Pigmented Spindle Cell Nevus of Reed. (August 2018) - VandenBoom, Timothy; Quan, Victor L.; Zhang, Bin; Garfield, Erin M.; Kong, Betty Y.; Isales, Maria C.; Panah, Elnaz; Igartua, Catherine; Taxter, Timothy; Beaubier, Nike; White, Kevin; Gerami, Pedram
Abstract : Recent molecular studies of spitzoid neoplasms have identified mutually exclusive kinase fusions involving ROS1, ALK, RET, BRAF, NTRK1, MET, and NTRK3 as early initiating genomic events. Pigmented spindle cell nevus (PSCN) of Reed is a morphologic variant of Spitz and may be very diagnostically challenging, having histologic features concerning for melanoma. Their occurrence in younger patients, lack of association to sun exposure, and rapid early growth phase similar to Spitz nevi suggest fusions may also play a significant role in these lesions. However, to date, there is little data in the literature focused on the molecular characterization of PSCN of Reed with next-generation sequencing. We analyzed a total of 129 melanocytic neoplasms with RNA sequencing including 67 spitzoid neoplasms (10 Spitz nevi, 44 atypical Spitz tumors, 13 spitzoid melanomas) and 23 PSCN of Reed. Although only 2 of 67 (3.0%) of spitzoid lesions had NTRK3 fusions, 13 of 23 (57%) of PSCN of Reed harbored NTRK3 fusions with 5′ partners ETV6 (12p13) in 2 cases and MYO5A (15q21) in 11 cases. NTRK3 fusions were confirmed with a fluorescent in situ hybridization break-apart probe. The presence of a NTRK3 fusion correlated with younger age ( P =0.021) and adnexal extension ( P =0.001). Other minor fusions identified in PSCN of Reed included MYO5A-MERTK (2), MYO5A-ROS1, MYO5A-RET, and ETV6-PITX3 leading to a total of 78% with fusions. Our study suggests that the majority of PSCN of Reed are the result of genomic fusions, and the most frequent and characteristic genomic aberration is an NTRK3 fusion. Abstract : Supplemental Digital Content is available in the text.